2019
DOI: 10.2174/1874210601913010228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Application Techniques on Nanohybrid Composite Restorations Clinical Success

Abstract: Introduction:Dental composites have been used as a restorative material for a long time. However, they have their limitations.Aims:This study evaluated the effects of placement techniques on the clinical performance of class I composite resin restorations.Methods:A total of 40 patients with split-mouth design participated in this study. Each patient had two fillings according to the placement technique (either bulk or incremental packing) of the composite resin restorations. Group (A): was packed by Tetric Evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In all included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the number of patients ranged from 22 to 86, with a follow-up time of between 6 months and 10 years. The countries, where the studies were carried out were: Turkey [ 14 , 16 , 18 , 20 , 27 ], Brazil [ 22 , 23 , 25 ], Germany [ 21 , 26 ], Sweden [ 17 , 19 ], Denmark [ 19 ], and Saudi Arabia [ 24 ]. Ten studies [ 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 ] reported that the mean age of the patients was between 7.41 and 55.30 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the number of patients ranged from 22 to 86, with a follow-up time of between 6 months and 10 years. The countries, where the studies were carried out were: Turkey [ 14 , 16 , 18 , 20 , 27 ], Brazil [ 22 , 23 , 25 ], Germany [ 21 , 26 ], Sweden [ 17 , 19 ], Denmark [ 19 ], and Saudi Arabia [ 24 ]. Ten studies [ 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 ] reported that the mean age of the patients was between 7.41 and 55.30 years.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of treated patients and restored teeth was 764 and 1915, respectively. In 5 studies [ 17 , 19 , 20 , 21 , 26 ], class I and class II restorations were performed, 3 studies [ 24 , 27 , 28 ] performed class I restorations, 6 studies [ 14 , 15 , 16 , 18 , 23 , 29 ] performed class II restorations, and 2 studies [ 22 , 25 ] performed non-carious cervical lesions (NCCL) restorations. Among the types of teeth restored, it was observed that the restorations were made in the permanent incisors, canines, premolars, and molars.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations